Marketing Communication Strategy for Female Weavers in Increasing Sales of Woven Songket in the Weaving Tourism Villages Batu Bara Regency North Sumatra Province - Rizqha Syaffira; Dewi Kurniawati; Nurbani (PT FORMOSA CENDEKIA GLOBAL, 2024)
This research aims to analyze marketing communication strategies, identify obstacles in marketing communication strategies, and find a model for marketing communication strategies. The research method used is qualitative with a qualitative descriptive approach. The subjects in this study consist of five main informants who are female weavers and marketers of woven songket fabric in Batu Bara, and there are two triangulation informants, namely the head of tourism and the chairman of the Tourism Awareness Group (Pokdarwis). This research utilizes communication theories with data collection methods including observation, in-depth interviews, and documentation. The results of this study indicate that female weavers have implemented the 4Ps approach: Product, Price, Place, and Promotion. The obstacles faced by the weavers include physical barriers, status barriers, and cultural barriers. The researcher also found a model in the marketing communication strategy used by the weavers, namely a marketing communication model in the form of face-to-face sales, where sales are made directly to potential buyers followed by community engagement by building good relationships with buyers , fellow weavers, and related parties. Followed by direct marketing divided into offline and online marketing, advertising on social media, and finally conducting sales promotions by offering discounts or promotions on a product.